Trudności we wdrażaniu systemu zarządzania środowiskowego jako bariera ekoinnowacyjnych rozwiązań - Dziedzic, Sylwia; Ziółkowski, Bożydar (Difficulties Connected with Implementation of Environmental Management System as a Barrier for Ecoinnovative Solutions, 2006)
There were presented results of realized research in depth. Thanks to them it was possible to obtain for example some data on difficulties which appeared during the implementation of the environmental management system according to the ISO 14001 standards. The identified difficulties are the main plot of this article.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1116, s. 695-701